A Novel Artificial Intelligence Approach to Optical Character Recognition of Conjunct Gujarati Script (International Journal of Scientific Research in Science and Technology, 2025)
This paper surveys recent advances in optical char- acter recognition (OCR) for the Gujarati script, with a focus on complex conjunct characters. Gujarati is an Indo-Aryan script spoken by ∼62 million people [1], [2], yet its OCR remains challenging due to intricate glyph shapes and extensive consonant clusters [3], [4]. We review how machine learning (ML), deep learning (DL), and NLP techniques have been applied to segment and recognize Gujarati text, especially conjunct lig- atures. Notable studies from 2012–2025 are examined, including ANN and CNN-based classifiers that achieve high accuracy on isolated conjuncts [3], [5]. Finally, ongoing challenges (data scarcity, variability of handwriting and fonts) and outline future directions such as transformer models and language-model integration for Gujarati OCR.